Fostering toddlers’ confidence development in their early childhood literacy - Rozaimie, Awang; Johari, Aiza; Ismail, Abdul; Unin, Norseha (Journal of Interdisciplinary Studies in Education, 2026)
The Reading Seed Programme (RSP) is an early childhood literacy initiative that has strong potential to support UNESCO’s Sustainable Development Goal 4 (SDG 4) by fostering a culture of reading. This programme, which begins as early as pregnancy, has demonstrated its effectiveness in building toddlers' confidence in reading through parental involvement. This study employed purposive sampling to gather data from parents involved in the RSP, revealing that the programme has a beneficial effect on children's early literacy development. However, several areas require improvement to enhance its effectiveness. These include tailoring the programme to individual learning needs, integrating robust monitoring systems, strengthening training for facilitators, establishing a strategic roadmap for outcomes, and clarifying the programme's attitudinal goals.